Pemberdayaan Warga Belajar Kejar Paket C Melalui Pelatihan Sulam Kruistik Untuk Meningkatkan Keterampilan Kewirausahaan di PKBM Winaya Bhakti - Ratna Sari Dewi; Yana Nursita (Yayasan Kawanad, 2026)
This Community Service Activity aims to improve cross-stitch embroidery skills through a structured training program designed to foster creativity and increase the income of students at the Winaya Bhakti Community Learning Center (PKBM), Banyusari Village, Karawang Regency. The rapid development of the industrial era demands that community members possess practical skills capable of supporting their economic independence. However, many students at this PKBM have not yet had adequate access to skill-based training relevant to their daily needs. Based on observations and interviews conducted with PKBM managers and tutors, it was found that students require training programs that not only provide motivation but also directly strengthen their practical abilities. Cross-stitch embroidery was selected as the focus of this training due to its accessible technique, low production cost, and promising market potential. Through this skill, community members are expected to develop themselves, build entrepreneurial confidence, and gradually improve their family's economic condition. The program was carried out in seven structured meetings, beginning with foundational concept-building and progressing to hands-on entrepreneurship practice through cross-stitch embroidery.